Impact of vibrations on the final characteristics of normal and self-compacting concrete - Juradin,Sandra (2014)
The quality and durability of normal concrete directly depends on the number and the shape of voids, so, in order to produce durable concrete, it is necessary to reduce the amount of air that is trapped inside the concrete, which is usually done by vibrating the concrete in the mixing stage or the casting stage. Self-compacting concretes are concretes that, in principle, don't require vibrating during casting. Such concretes possess enough compactness and flowability through gravity that during pouring they fill all the space in the formwork. However, it is frequently the case that the ideal self-compacting concrete that is produced in a laboratory cannot be produced on a construction site so such concretes require additional vibrations. The work examines the impact that the introduction of vibrations during mixing and during casting has on the final appearance and the compressive strength of normal and self-compacting concretes. Achieved results confirm that vibrating during the mixing stage can improve the workability of fresh concrete but not its final strength, especially for self-compacting concretes, while vibrating in the casting stage significantly contributes to the final strength of the concrete.